2021
DOI: 10.1164/rccm.202007-2701oc
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Oscillatory Volumes into the Preterm Lung during Noninvasive High-Frequency Ventilation

Abstract: Rationale: There is increasing evidence for a clinical benefit of noninvasive high-frequency oscillatory ventilation (nHFOV) in preterm infants. However, it is still unknown whether the generated oscillations are effectively transmitted to the alveoli. Objectives: To assess magnitude and regional distribution of oscillatory volumes (VOsc) at the lung level. Methods: In 30 prone preterm infants enrolled in a randomized crossover trial comparing nHFOV with nasal continuous positive airway pressure (nC-PAP), elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 50 publications
2
37
0
Order By: Relevance
“…Therefore, these differences may be due to the airway pressure itself rather than the pressure waveform generated from the two NIV modes. The nHFOV group had a lower rate of air leak syndrome than the BiPAP group, and we suspected that this may be due to the small tidal volumes used, which results in less pressure-andvolume trauma from nHFOV (21). High-frequency oscillation ventilation is a type of oscillation with a high frequency of air flow.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these differences may be due to the airway pressure itself rather than the pressure waveform generated from the two NIV modes. The nHFOV group had a lower rate of air leak syndrome than the BiPAP group, and we suspected that this may be due to the small tidal volumes used, which results in less pressure-andvolume trauma from nHFOV (21). High-frequency oscillation ventilation is a type of oscillation with a high frequency of air flow.…”
Section: Discussionmentioning
confidence: 99%
“…The setup of the original study has been described previously 7 8. Infants were eligible if they were (1) born <30 weeks’ gestation, (2) older than 7 days, (3) between 26 and 34 weeks’ postmenstrual age, (4) extubated for more than 24 hours and (5) clinically stable while receiving nCPAP support.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, our group provided evidence of substantial transmission of oscillatory volumes into the lung of preterm infants on nHFOV. We demonstrated that compared with the regional distribution of tidal breaths, oscillations preferentially reached the right and non-gravity-dependent (NGD) lung regions 8. However, the effects of these differences on overall ventilation and lung aeration remain unclear.…”
Section: Introductionmentioning
confidence: 92%
“…The meta-analysis by Li et al showed that compared to nCPAP and BiPAP, nHFOV may significantly increase the removal of carbon dioxide and, thus, reduce the need for intubation and IMV in premature infants with RDS [45]. Interestingly, although the actual transmission of oscillations to the alveoli was considered to be minimal with nHFV [108], a recently published study in preterm infants on nHFOV was able to prove a substantial transmission of oscillatory volumes into the lung, preferentially into the right, non-gravitydependent areas [112]. Questions remain, though, regarding the most appropriate settings, ventilator type, and diseases best treated using nHFV [113].…”
Section: Nasal High-frequency Ventilationmentioning
confidence: 99%